Forensic Enquiry as a Method for Objective Evidence Verification - KOSTENKO, Roman V.; TOKARENKO, Ekaterina S. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).17, 2018)
The article considers relevant aspects of the essence of forensic enquiry in criminal cases. The author analyzes the attributes of forensic enquiry and justifies its attribution to investigative actions, the main objective of which is to verify the evidence: (1) purpose - the verification of evidence; (2) the basis for forensic enquiry is the data obtained by procedural means; (3) the supporting role of evidence obtained as a result of the expert study; (4) comparative analysis is the main method of study used in this investigative action; (5) the complex nature of forensic enquiry. The article gives the examples from court practice, illustrating the importance of forensic enquiry in establishing the circumstances to be proved, as well as the identification of objective causal relationships between the material, ideal traces and the event of crime reflected in the surrounding reality.